2020
DOI: 10.3390/molecules25204837
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Partial Corticotomy on the Rate of Maxillary Canine Retraction: Clinical and Radiographic Study

Abstract: The study aimed to evaluate, clinically and radiographically, the effect of partial corticotomy of the buccal plate distal to the canine on the rate of maxillary canine retraction. A clinical trial with the split-mouth design was conducted among twenty orthodontic patients, recommended for first premolar extraction with an age range from 13 to 21 years, selected from patients seeking orthodontic treatment in private dental clinics in Jeddah, Kingdom of Saudi Arabia. After extraction of the maxillary right and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Baeshen (2020) conducted a partial buccal plate corticotomy distal to the lingual vertical and subapical incisions, and the lingual flap was not raised [30]. This technique revealed that the rate of canine retraction on the corticotomy side was substantially greater than on the C Side [30].…”
Section: Corticotomiesmentioning
confidence: 99%
“…Baeshen (2020) conducted a partial buccal plate corticotomy distal to the lingual vertical and subapical incisions, and the lingual flap was not raised [30]. This technique revealed that the rate of canine retraction on the corticotomy side was substantially greater than on the C Side [30].…”
Section: Corticotomiesmentioning
confidence: 99%
“…Several methods have emerged to improve orthodontic tooth movement and shorten the duration of orthodontic treatment, with surgical methods being the most popular, including traditional corticotomy [6,7], and interseptal alveolar surgery. However, these techniques have shown low acceptance among patients due to their invasive nature and postoperative complications.…”
Section: Introductionmentioning
confidence: 99%